DC Motor Speed Control System Using Pulse Width Modulation (PWM) On Electric Motorcycles - Beni Satria; Hermansyah Alam; Dalimunthe, Erpandi; M. Iqbal; Berthauli S. (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
The need for efficient and environmentally friendly electric two-wheeled vehicles is increasing along with awareness of the impact of pollution. One of the main challenges in the development of electric vehicles is controlling the speed of DC motors precisely and efficiently. This study aims to design and implement a DC motor speed control system on a two-wheeled vehicle using the Pulse Width Modulation (PWM) method. PWM was chosen because of its ability to regulate motor power efficiently through variations in the width of the digital signal pulse, thereby reducing energy waste and excess heat. The research methods include designing a microcontroller-based PWM circuit, simulating system performance using MATLAB/Simulink software, and direct testing on DC motors with input voltage variations of 3–12 volts. The test results show that the system is able to produce a linear speed response, with an increase in motor rotation from 0 rpm at 3 volts to 1500 rpm at 12 volts. This system is also proven to be energy efficient with power efficiency reaching 85% and reducing motor heat by 20%. Thus, the implementation of PWM as a DC motor speed controller on a two-wheeled electric vehicle not only improves performance and responsiveness, but also contributes to environmental sustainability.